2022
DOI: 10.1002/aenm.202200204
|View full text |Cite
|
Sign up to set email alerts
|

High‐Ranged ZT Value Promotes Thermoelectric Cooling and Power Generation in n‐Type PbTe

Abstract: Excellent thermoelectric cooling and power generation are simultaneously realized in an n‐type PbTe‐based thermoelectric material. The cooling temperature difference (ΔT) of ≈15.6 K, maximum power density of ≈0.4 W cm−2 and conversion efficiency of ≈1.5% with TC = 295 K and TH = 765 K can be obtained in a single‐leg device composed of PbTe‐30%SnSe‐1.5%Cu. This advanced thermoelectric performance in n‐type PbTe‐30%SnSe‐1.5%Cu mainly originates from its high‐ranged ZT value achieved through optimizing its bandga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 57 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…6b ). Moreover, the down-and-up tendency in temperature-dependent electrical conductivity and Seebeck coefficient indicates the dynamic doping behavior of Cu interstitials in lead chalcogenides as proved in our previous works 20 , 42 , 43 . Benefiting from the Cu interstitial doping, the power factor in Pb 1.02 Se 0.72 Te 0.20 S 0.08 - x %Cu ( x = 0–0.40) is obviously enhanced in the whole-temperature range.…”
Section: Resultssupporting
confidence: 77%
“…6b ). Moreover, the down-and-up tendency in temperature-dependent electrical conductivity and Seebeck coefficient indicates the dynamic doping behavior of Cu interstitials in lead chalcogenides as proved in our previous works 20 , 42 , 43 . Benefiting from the Cu interstitial doping, the power factor in Pb 1.02 Se 0.72 Te 0.20 S 0.08 - x %Cu ( x = 0–0.40) is obviously enhanced in the whole-temperature range.…”
Section: Resultssupporting
confidence: 77%
“…However, our results show that the carrier concentration has an obvious decreasing trend with temperature rising, indicating that the cation vacancies may be excited or electrons may be redistributed among the multiple conduction bands at higher temperatures 46 . To verify this, we compare the temperature-dependent behavior of Hall carrier mobility μ H and weighted mobility μ W (a mobility includes the effective mass m * of electronic density of states, and is widely used in thermoelectric systems to evaluate the carrier transport behavior) 3 , 38 , 47 , 48 , as shown in Fig. 2d .…”
Section: Resultsmentioning
confidence: 99%
“…The thorny problems of energy shortage and environmental pollution have been challenging the sustainable development. Thus, thermoelectric materials have gained increasing attention because they provide an alternative way of energy utilization by realizing the direct and reversible conversion between heat and electricity 1 3 . The efficiency of thermoelectric devices depends on the material’s dimensionless figure of merit, ZT = S 2 σT /( κ lat + κ ele ), where S , σ , S 2 σ , T , κ lat and κ ele represent Seebeck coefficient, electrical conductivity, power factor, absolute temperature, lattice thermal conductivity and electronic thermal conductivity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, strategies for improving carrier mobility have been attempted to realize better TE cooling in various systems, such as textured Bi 2 Te 3 -based alloys 125,126 and defect-modulated PbTe. 19…”
Section: Establishing Better Thermoelectric Coolingmentioning
confidence: 99%
“…5,13–18 However, there are still some problems to be solved before their large-scale commercialization. Moreover, recent research revealed that the traditional mid-temperature PbQ (Q = Te, Se, S) systems also possess extraordinary TE performance near room temperature with extremely high carrier mobility, 19 demonstrating great potential as new TE cooling materials, with practical devices to be further constructed.…”
Section: Introductionmentioning
confidence: 99%